Cybertheology and the Ethical Dimensions of Artificial Superintelligence: A Theological Inquiry into Existential Risks - Ted Peters (Khazanah Theologia, 2024)
Purpose: This study explores the role of cybertheology in addressing the ethical and societal challenges posed by Artificial Superintelligence (ASI), which has the potential to surpass human cognitive capabilities, heralding a profound cultural and existential crisis. It integrates theological anthropology to assess the implications of a posthuman future. Methodology: Utilising a comprehensive literature review, the research examines technological, philosophical, and theological perspectives through primary and secondary sources, including influential works by futurists and ethicists. The methodology aims to uncover the nuanced discourse surrounding the development of ASI and its potential impacts. Findings: The analysis reveals a narrative marked by speculative optimism and significant existential concerns regarding ASI. A critical gap in the existing ethical discourse is identified, highlighting the necessity for a grounded ethical framework that addresses the profound implications of superintelligent entities on human dignity and societal norms. Research Implications: The findings emphasise the urgent need to incorporate robust ethical considerations into the development and deployment of ASI. Cybertheology is presented as a vital framework for ensuring that ASI technologies align with human values and theological insights, thus providing a valuable lens through which to view the integration of superintelligence into society. Originality/Value: This paper contributes to academic and policy discussions on ASI by promoting cybertheology as a crucial perspective in ethical deliberations. It enriches scholarly dialogues by linking technological advancements with theological and ethical evaluations, proposing that cybertheology can play a pivotal role in shaping policies that govern ASI technologies. This approach ensures that technological progress is compatible with humanistic values, fostering a holistic understanding of ASI's potential impact on humanity.